Humans tend to share food more generously than money and other objects: Preliminary evidence. (5th May 2021) - Sorokowska, Agnieszka; Marczak, Michalina; Misiak, Michał; Oleszkiewicz, Anna; Niemczyk, Agnieszka; Wróbel, Monika; Sorokowski, Piotr
Abstract: Food‐sharing is an especially important component of human cooperation, trust and altruism, and certain characteristics of food as compared to other objects may increase the likelihood of food transfers to other individuals. Consequently, people should exhibit higher generosity when sharing food than when sharing other goods (like money or inedible items). We tested this prediction in a series of natural experiments. In Study 1, we found that people ( N  = 114) were more likely to buy a bread roll for a confederate dressed up as a poor‐looking person than to give money for a bread roll or money to this person. In Study 2, 239 participants were more likely to donate food than non‐food items such as hygienic products or school accessories to a social welfare center. Finally, in Study 3, 226 subjects could share perishable, edible items (apples), coupons for apples or inedible items (pens) with fellow students, and there were no significant differences in generosity between these conditions. Overall, our results suggest that humans might exhibit a food‐sharing preference in certain conditions, especially when they share objects that belong to them and when they have a choice between sharing food and non‐food items. However, further studies are necessary to confirm this notion, to explore the characteristics of food that make sharing it particularly probable, and to understand potential mechanisms underlying this tendency.